Current Mesalazine Products: Differences in Enteric-Coated Dosage Forms and Pharmaceutical Risks of Clinical Efficacy Reduction (Review) - S. Yu. Serebrova; V. V. Evteev; E. Yu. Demchenkova; M. V. Zhuravleva; A. B. Prokofiev (Безопасность и риск фармакотерапии, 2024)
INTRODUCTION. Oral mesalazine (5-aminosalicylic acid) products are commonly used to treat inflammatory bowel disease, in particular,  ulcerative  colitis.  The  clinical  efficacy  of  these  medicinal  products  depends  directly on the composition and properties of the polymers used to deliver mesalazine to the affected areas of the colon. However, the information that has been accumulated to date suggests that the release of mesalazine from enteric-coated dosage forms in gastrointestinal tract simulations differs from that in the actual human gastrointestinal tract, which necessitates further research.AIM. This study aimed to systematise information on the polymers used in the enteric coating of mesalazine products and to assess the pharmaceutical risks associated with the potential reduction in the efficacy of ulcerative colitis therapy.DISCUSSION. The absorption and metabolism of mesalazine dictate the need for enteric-coated dosage forms to deliver the active substance directly to the affected areas of the colon. The most common polymer used in the manufacturing of oral mesalazine products is a methacrylic acid–methyl methacrylate copolymer with a monomer ratio of 1:1, which releases the active substance at pH 7.0. Some manufacturers use a methacrylic acid–ethyl acrylate copolymer with a monomer ratio of 1:1, which dissolves at pH 5.5. The gastrointestinal pH in patients with  inflammatory  bowel  disease  may  vary  in  wide  and  often  overlapping  ranges  depending on the organ (1.0–7.0 in the stomach, 5.0–6.2 in the duodenum, 6.1–7.1 in the jejunum, 7.4–7.5 in the ileum, and 5.7–7.5 in the colon with a possibility of acidification in ulcerative colitis patients). The rate of gastrointestinal transit varies widely as well. These factors may cause premature release of mesalazine in the stomach or the small intestine before the dosage form reaches the colon, which poses the risks of reduced clinical efficacy and systemic adverse effects.CONCLUSIONS. In the vast majority of ulcerative colitis patients, the methacrylic acid–methyl methacrylate copolymer provides targeted delivery of 5-aminosalicylic acid from tablets and granules, facilitating its local action in the colon. However, developers and manufacturers selecting the polymer for enteric coating of oral mesalazine dosage forms should consider the pharmaceutical risks associated with reduced clinical efficacy.